The effects of education on cognition in older age: Evidence from genotyped Siblings. (July 2021) - Fletcher, Jason; Topping, Michael; Zheng, Fengyi; Lu, Qiongshi
Abstract: A growing literature has sought to tie educational attainment with later-life cognition and Alzheimer's disease outcomes. This paper leverages sibling comparisons in educational attainment as well as genetic predictors (polygenic scores) for cognition, educational attainment, and Alzheimer's disease to estimate effects of educational attainment on cognition in older age in the United Kingdom. We find that the effects of education on cognition are confounded by family background factors ( 40%) and by genetics (<10%). After adjustments, we continue to find large effects of education. College graduates have cognition scores that are approximately 0.75 SD higher than those who report no credentials. We also find evidence that educational effects on cognition are smaller for those with high polygenic scores for Alzheimer's disease. Highlights: Explores associations between educational attainment and later life cognition. Uses large scale sibling comparisons in the UK Biobank to control family background. Examines genetic confounding by controlling for polygenic scores. Finds both large confounding and large remaining associations between education and cognition.